Estimating age using permanent molars and third cervical vertebrae shape with a novel semi-automated method. (August 2018) - Mânica, Scheila; Wong, Ferranti S.L.; Davis, Graham; Liversidge, Helen M.
Abstract: Estimating chronological age accurately in young adults is difficult and additional methods are required to increase the accuracy. This study explored a new semi-automated method to assess shape change of third cervical vertebra (C3) with age in the living; comparing this as a method to determine whether individuals could be categorised into being less than 18 years of age (<18), or at least 18 years of age (≥18) with tooth formation of the second and third mandibular molars (M2 and M3). The sample was panoramic and lateral skull radiographs of 174 dental patients (78 males, 96 females aged 15–22 years). Twelve variables were compared in two age categories: younger than 18 and at least 18 years of age in males and females separately using a t -test. Tooth formation of M2 and M3 was assessed. Mean values of eight variables of C3 in males and one variable in females were significantly different between the two age categories (p < 0.05). Results for males showed that the best age indicator for age ≥18 was the ratio between height and width of C3 and for females, the ratio between diagonals. Results for molars showed that M2 was mature in 69% of males and 83% of females, within the expected age range of 14–16 years. M3 was highly variable ranging from stages 6–14 for both; M3 was missing in 24% of males and 28% of females and mature in 14% of males and 15% of females. The conclusion was that shape change of C3 has potential as an additional method to group individuals <18 and ≥ 18 years of age. Highlights: Third cervical vertebral shape can discern between individuals age<18 and ≥ 18 years. Useful in cases when the second molar is mature or the third molar is missing. Reduces the impact of highly variable third molar development in age estimation.